Patient satisfaction with epilepsy surgery: what is important to patients. Issue 5 (21st November 2018) - Lunney, Meaghan; Wahby, Sandra; Sauro, Khara M.; Atkinson, Mark J.; Josephson, Colin B.; Girgis, Fady; Singh, Shaily; Patten, Scott B.; Jetté, Nathalie; Sajobi, Tolulope T.; Hader, Walter; Wiebe, Samuel
ABSTRACT: Aims . Patient satisfaction with therapeutic interventions is an important outcome of care. Although generic measures of patient satisfaction exist, there is no validated scale for measuring patient satisfaction with epilepsy surgery. We aimed to systematically obtain patient‐identified factors related to satisfaction with epilepsy surgery as a means of informing clinicians about the ways that patients evaluate outcomes of their treatment and as a conceptual basis for the future development of epilepsy surgery patient satisfaction scales. Methods . Focus group discussions with epilepsy surgery patients ( n =9) were conducted to identify themes relevant to patient satisfaction with epilepsy surgery and to draft initial items of importance. Consensus methodology (Delphi technique) was used to obtain expert opinion ( n =13) to refine the items. Member‐checking with focus group participants was performed to ensure the identified items were relevant, clear, and inclusive. Results . A list of 31 items embodied 12 themes related to patient‐reported satisfaction with epilepsy surgery. These included adverse effects, medical care or rehabilitation, seizure control, post‐operative recovery, anti‐seizure medication, independence, seizure worry, ability to drive, social relationships, self‐confidence, improved cognitive function, and improved physical health. Conclusions . This study used a systematic approach to identify factors that are important to patients when assessing satisfaction with epilepsy surgery. This knowledge can assist clinicians caring for these patients and is also a critical step towards the validation of a formal scale to assess satisfaction with epilepsy surgery.